Lipid packing and cholesterol content regulate membrane wetting and remodeling by biomolecular condensates - Agustín Mangiarotti; Elias Sabri; Kita Valerie Schmidt; Christian Hoffmann; Dragomir Milovanovic; Reinhard Lipowsky; Rumiana Dimova (Nature Communications)
Abstract Biomolecular condensates play a central role in cellular processes by interacting with membranes driving wetting transitions and inducing mutual remodeling. While condensates are known to locally alter membrane properties such as lipid packing and hydration, it remains unclear how membrane composition and phase state in turn affect condensate affinity. Here, we show that it is not only the membrane phase itself, but rather the degree of lipid packing that determines the condensate affinity for membranes. Increasing lipid chain length, saturation, or cholesterol content, enhances lipid packing, thereby decreasing condensate interaction. This regulatory mechanism is consistent across various condensate-membrane systems, highlighting the critical role of the membrane interface. In addition, protein adsorption promotes extensive membrane remodeling, including the formation of tubes and double-membrane sheets. Our findings reveal a mechanism by which membrane composition fine-tunes condensate wetting, highlighting its potential impact on cellular functions and organelle interactions.